Kompetisi dan Inovasi di Indonesia: Bukti Empiris dari Industri Manufaktur - Rachmaidi, Mohammad Adhi; Lubis, Andi Fahmi (UI Scholars Hub, 2019)
This paper studies empirical relationship between competition and innovation in Indonesia using micro data BPS. Lack of innovation data has requires this paper to use R&D expenditure as innovation in year of data avaibility. Competition is estimated by computing profit elasticity, based on idea of efficiency. Inverted-U shape tested with technology spread within industries at which effect of competition and innovation can turn from positive to negative. Empirical evidence shows that relationship between competition and innovation is inverted-U with very low optimal point. This means that very few industries can increase innovation and almost all industries will reduce innovation as competition increases.